Effect of SLCO1B1 T521C on Statin‐Related Myotoxicity With Use of Lovastatin and Atorvastatin. Issue 3 (23rd July 2021) - Lu, Brian; Sun, Laura; Seraydarian, Manuel; Hoffmann, Thomas J.; Medina, Marisa W.; Risch, Neil; Iribarren, Carlos; Krauss, Ronald M.; Oni‐Orisan, Akinyemi
Abstract : The association between the c.521T>C variant allele in SLCO1B1 (reference single nucleotide polymorphism (rs)4149056) and simvastatin‐induced myotoxicity was discovered over a decade ago; however, whether this relationship represents a class effect is still not fully known. The aim of this study was to investigate the relationship between rs4149056 genotype and statin‐induced myotoxicity in patients taking atorvastatin and lovastatin. Study participants were from the Genetic Epidemiology Research on Adult Health and Aging (GERA) cohort. A total of 233 statin‐induced myopathy + rhabdomyolysis cases met the criteria for inclusion and were matched to 2, 342 controls. To validate the drug response phenotype, we replicated the previously established association between rs4149056 genotype and simvastatin‐induced myotoxicity. In particular, compared with homozygous T allele carriers, there was a significantly increased risk of simvastatin‐induced myopathy + rhabdomyolysis in homozygous carriers of the C allele (CC vs. TT, odds ratio [OR] 4.62, 95% confidence interval [CI] 1.58–11.90, P  = 0.003). For lovastatin users, homozygous carriers of the C allele were also at increased risk of statin‐induced myopathy + rhabdomyolysis (CC vs. TT, OR 4.49, 95% CI 1.68–10.80, P  = 0.001). In atorvastatin users, homozygous carriers of the C allele were twice as likely to experience statin‐induced myopathy, though this association did not achieve statistical significance (CC vs. TT, OR 2.00, 95% CI 0.44–6.59, P  = 0.30). In summary, our findings suggest that the association of rs4149056 with simvastatin‐related myotoxicity may also extend to lovastatin. More data is needed to determine the extent of the association in atorvastatin users. Altogether, these data expand the evidence base for informing guidelines of pharmacogenetic‐based statin prescribing practices.